Prior chemotherapy deteriorates T-cell quality for CAR T-cell therapy in B-cell non-Hodgkin’s lymphoma - Annette Künkele; Andrea Stroux; Olaf Penack; Lars Bullinger; Benedikt Obermayer; Charlotte Junkuhn; Phillip Schiele; Anna Luzie Walter; Frederik Hamm; David Busch; Mareike Frick; Frederik Damm; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background Chimeric antigen receptor (CAR) T-cell therapy depends on T cells that are genetically modified to recognize and attack cancer cells. Their effectiveness thus hinges on the functionality of a patient’s own T cells. Since CAR T-cell therapy is currently only approved for advanced cancers after at least one line of chemotherapy, we evaluated the potential negative effects of prior exposure to chemotherapy on T-cell functionality.Methods We studied T cells of two B-cell non-Hodgkin’s lymphoma patient cohorts, one collected before treatment (pre-therapy) and the other after one or more (median 3) lines of chemotherapy (post-therapy). Leveraging advanced multiparameter flow cytometry, single-cell RNA sequencing (scRNA-seq), whole-genome DNA methylation arrays and in vitro functionality testing of generated CAR T cells, we compared patient samples in their suitability for effective CAR T-cell therapy.Results We discovered significant modifications in T-cell subsets and their transcriptional profiles secondary to chemotherapy exposure. Our analysis revealed a discernible shift towards phenotypically more differentiated T cells and an upregulation of markers indicative of T-cell exhaustion. Additionally, scRNA-seq and DNA methylation analyses revealed gene expression and epigenetic changes associated with diminished functionality in post-therapy T cells. Cytotoxicity assays demonstrated superior killing efficacy of CAR T cells derived from treatment-naïve patients compared with those with chemotherapy history.Conclusions These findings corroborate that employing T cells collected prior to frontline chemotherapy could enhance the effectiveness of CAR T-cell therapy and improve patient outcomes.